Literatura en transición – Del binarismo entre lo “culto” y lo popular a la vanguardia en guaraní - Carla Daniela Benisz (Centre de Recherches sur les Mondes Américains, 2020)
The article presents a review of the scene of Paraguayan Literature around the hinge date of February, 3th. 1989. It is when the long dictatorship of Alfredo Stroessner ends and new scenery begins for Paraguayan society and culture. In order to offer a representative panorama of this period, I will approach here some concrete examples of the changes that take place in the intellectual field. Firstly, I will develop two of the measures taken by the Paraguayan State during the first years of democracy: the creation of the National Prize for Literature and the recognition of Guarani as official language. Secondly, I will approach the new literary aesthetics that occur in parallel and that have in common the literary and "modernizing" use of Guaraní.